C23 HOW TO IMPROVE ADHERENCE TO ESC HF GUIDELINES THE PONTE (PDTA FOR INTEGRATED FOLLOW–UP TERRITORY HOSPITAL OF THE PATIENT WITH CARDIAC HEART FAILURE) PROJECT. (18th May 2022) - De Gennaro, L; Donadeo, V; Ruggero, M; Tota, F; Sergio, M; De Laura, D; Cavallari, D; Resta, M; Ricci, G; Licurgo, L; Buquicchio, F; Corriero, F; et al.
Abstract: Background: A careful and integrated follow up after hospitalization for heart failure (HF) may represent a feasible strategy to optimize the adherence to ESC guidelines and reduce the occurrence of adverse events (mortality, re–hospitalizations). Methods: A strict integration between hospital and local health district proximity office cardiologist through an integrated clinical data sharing software has been implemented in Apulia region, Italy, in order to optimize the management of the HF patient after an hospitalization: the PONTE (PDTA FOR INTEGRATED FOLLOW–UP TERRITORY HOSPITAL OF THE PATIENT WITH CARDIAC HEART FAILURE) (bridge) project. As until December 2021, 1200 patients with HF have been enrolled in the project, both with reduced (HFrEF) and preserved ejection fraction (HFpEF). Adherence to ESC HF guidelines in HFrEF patients before vs after December 2020 was compared. Results: In the HFrEF population (56%) the mean age was 63 years, 38% were hypertensive, 15% diabetic, 40% had ischemic heart disease, 42% were previously treated with coronary angioplasty, 56% had an ICD/CRT, 22% had atrial fibrillation. Mean NYHA class was 2.2, mean LVEF 30%, mean NT–proBNP values 4027 pg/mL, mean serum creatinine 1 mg/dL, 91% were taking beta–blockers (BB), 86% mineral corticoid receptor antagonists (MRA), 98% ACE–inhibitors/angiotensin–receptor–antagonists/neprilysin and angiotensin receptor antagonists (ACE/ARB/ARNI), and 13% ARNI. Compared to patients enrolled before 2020, ARNI prescription increased in 2021 (60% vs 13%, p < 0.001); in 30% ARNI were prescribed in hospital before discharge. Furthermore, in 10% of the population (most diabetics), sodium glucose cotransporter type 2 inhibitors (SGLT2i) have been prescribed as indicated by the latest ESC 2021 guidelines. Conclusions: The implementation the PONTE project shows an improved adherence to ESC HF guidelines.